PENGOLAHAN LIMBAH MENJADI PUPUK ORGANIK DAN EKOBRIK DI LINGKUNGAN UNIVERSITAS MUHAMMADIYAH MATARAM - Marianah, Marianah; Hardiyanti, Titi; Rukmana, Rukmana; Ikbal, Muhamad; Apriyandi, Erwin; Sakdiah, Halimatus; Abadi, Lukman; Jaka, Heri susanto; Saputra, Saputra; Oktaviani, Baiq Santi; Sudirman, Sudirman; Ridho, Ridho; hanafiah, Muhammad Ali; Vicakhsana, I Gede Satria; Wibawa, Lalu Elwan; Hidayatullah, Farid; Sumarlin, Lalu; Abdillah, Wisnu Arya; Gatama, Arya; Buana, Lalu Agung Gede; Suwati, Suwati; Muanah, Muanah (Universitas Muhammadiyah Mataram, 2022)
Waste is a by-product of all activities carried out while on campus, both in the form of organic and non-organic waste. High volume waste can be a problem for the environment so it needs to be managed properly. The purpose of this mentoring activity is to equip the cleaning staff so that waste in the University of Muhammadiyah Mataram (UMMAT) can be managed into organic fertilizer and ecobricks. There are three methods of mentoring, namely socialization, training, and evaluation. The socialization was carried out to provide an overview to participants regarding waste processing technology. Meanwhile, the training is to prove that the theoretical ability of partners from socialization can be applied to training and evaluation is carried out to see the level of success of mentoring activities. After the mentoring activities were carried out, it was proven that the knowledge of partners had increased and the waste within the Muhammadiyah University of Mataram was able to be managed slowly in the manufacture of organic fertilizers and echobrick.